Performance evaluation and customer satisfaction on mutual fund of Investment corporation of Bangladesh (lCB) - Rahman, Saifur (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.